Chede Dev Temple at the entarnce of Worli village - Mumbai Archive Project Team (Jio Institute, 2024)
Chede Dev Temple is located at the entrance of Worli village. The doorway is flanked by a pair of stone deepasthambs (lamp columns). The triangular niches cut into the deepastambhas are used for placing diyas (oil lamps).